Robust Blind Frequency and Transition Time Estimation for Frequency Hopping Systems. (10th November 2010) - Fu Fu, Kuo-Ching Kuo-Ching; Chen Chen, Yung-Fang Yung-Fang
Abstract : In frequency hopping spread spectrum (FHSS) systems, two major problems are timing synchronization and frequency estimation. A blind estimation scheme is presented for estimating frequency and transition time without using reference signals. The scheme is robust in the sense that it can avoid the unbalanced sampling block problem that occurs in existing maximum likelihood-based schemes, which causes large errors in one of the estimates of frequency. The proposed scheme has a lower computational cost than the maximum likelihood-based greedy search method. The estimated parameters are also used for the subsequent time and frequency tracking. The simulation results demonstrate the efficacy of the proposed approach.